БОШЛАНҒИЧ СИНФ ЎҚУВЧИЛАРИ ЖИСМОНИЙ ТАРБИЯСИ ШАКЛЛАРИ - Сафин, Д.А.; Ерйигитов, Д.Х. (SCIENCE and SOCIETY, 2020)
The article deals with the issues of the physical form of primary school students and it is emphasized that the social conditions of life of people are crucial in physical development.